2016
DOI: 10.1007/s00339-016-0253-y
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of magnetocaloric properties of arc-melted and spark plasma-sintered LaFe11.6Si1.4

Abstract: LaFe 11.6 Si 1.4 alloy has been synthesized in polycrystalline form using both arc melting and spark plasma sintering (SPS). The phase formation, hysteresis loss and magnetocaloric properties of the LaFe 11.6 Si 1.4 alloys synthesized using the two different techniques are compared. The annealing time required to obtain the 1:13 phase is significantly reduced from 14 days (using the arc melting technique) to 30 min (using the SPS technique). The magnetic entropy change (DS M ) for the arc-melted LaFe 11.6 Si 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The authors reported a thermal conductivity of 6 W mK –1 and reproducible Δ T ad of 5.4 K for a magnetic field change of 1.93 T. They also applied a method for processing magnetocaloric regenerators via metallic additive manufacturing. The method was implemented by Shamba et al, who processed LaFe 11.6 Si 1.4 alloys using spark plasma sintering. A comprehensive experimental study on the use of Gd was performed by Trevizoli et al In the first part of the study, the authors fabricated stainless‐steel regenerator samples with different geometries: parallel plate, pin array, and sphere‐packed bed.…”
Section: Magnetocaloric Refrigeration and Heat Pumpingmentioning
confidence: 99%
“…The authors reported a thermal conductivity of 6 W mK –1 and reproducible Δ T ad of 5.4 K for a magnetic field change of 1.93 T. They also applied a method for processing magnetocaloric regenerators via metallic additive manufacturing. The method was implemented by Shamba et al, who processed LaFe 11.6 Si 1.4 alloys using spark plasma sintering. A comprehensive experimental study on the use of Gd was performed by Trevizoli et al In the first part of the study, the authors fabricated stainless‐steel regenerator samples with different geometries: parallel plate, pin array, and sphere‐packed bed.…”
Section: Magnetocaloric Refrigeration and Heat Pumpingmentioning
confidence: 99%
“…For the traditional magneto-caloric materials, such as LaFe 11.6 Si 1.4 and MnAs, the Curie temperature also has to be tuned using dopants such as Co, H and Si, which moves the T c to around 280-300 K, but this decreases the refrigerant capacity. At 2 T, the refrigerant capacity of LaFe 11.6 Si 1.4 is in the range 100-150 J K −1 [11,29,33] for a temperature range between 180 K and 220 K and for MnFeP 1−x As x is in the range 200-250 J K −1 [11,34] for a temperature range 260-340 K. Thus they are higher than those measured for the HEAs, but have the disadvantages mentioned above, meaning the search for new materials is still ongoing, and HEAs may hold the key in the long run.…”
Section: Magneto-caloric Propertiesmentioning
confidence: 99%